Contribution to the understanding of the relationship between mechanical and dielectric strengths of Alumina - Malec, D.; Bley, V.; Talbi, F.; Lalam, F.
The experimental evolutions of the Alumina dielectric strength versus thickness (127 ?m to 2.54 mm), purity (92 percent , 96 percent and 99.5 percent ) and crystallography (single or polycrystal)have been investigated. In order to find crucial information about the mechanism responsible for the dielectric breakdown, optical and scanning electron micrograph observations have also been performed. Each breakdown channel was found to be terminated by a crater from which matter has been extracted during the breakdown process. Investigations have been focused on the breakdown path, on the evolution of the crater size versus sample thickness and on the location of molten matter after breakdown. The results tend to confirm that the dielectric breakdown of Alumina is probably originated from a mechanical failure induced by electromechanical forces acting during the voltage application.
Keywords: FAILURE ANALYSIS; DIELECTRIC PROPERTIES; AL2O3; INSULATORS; TOUGHNESS